Post-programme surveillance report (Publications Office of the European Union, 2024)
Staff from the European Commission (EC), in liaison with staff from the European Central Bank (ECB), undertook the nineteenth post-programme surveillance (PPS) mission to Portugal from 28 February to 1 March 2024. Staff from the European Stability Mechanism (ESM) participated in the meetings on aspects related to the ESM's Early Warning System. IMF staff also participated in the meetings. Under PPS, the Commission carries out regular review missions to euro area Member States that have had a financial assistance programme. The objective of the PPS missions is to assess the economic, fiscal and financial situation to ensure the Member State maintains its capacity to service its debt. From mid-2011 until mid-2014 Portugal implemented an economic adjustment programme with the European Union and the International Monetary Fund (IMF). The overall financial package was agreed at EUR 78 billon. In June 2014, Portugal exited the programme. This report reflects information available and policy developments that have taken place until 30 April 2024. The macroeconomic and budgetary projections, including those underlying the debt sustainability analysis, are in line with the Commission 2024 spring forecast released on 15 May 2024 (with cut-off date 30 April 2024).
10.2765/810761
Keywords: Graue Literatur; EU alert system; economic reform; financial aid; structural adjustment; public debt; public finance; economic growth; economic policy; fiscal policy; financial policy; structural policy; economic forecasting; macroeconomics; European Stability Mechanism; financial stability; Portugal; report